Determinants of MSME Taxpayer Compliance with Moderating Variables of Tax Incentive Utilization in Manado City - Melisa Fransisca Lo; Herman Karamoy; Hendrik Gamaliel (Dinasti Publisher, 2023)
Objective: The purpose of this study was to analyze the effect of tax socialization, tax knowledge, and service quality on MSME taxpayer compliance and to test whether tax incentives were able to moderate the effect of these factors on MSME taxpayer compliance in Manado City. Research Design & Methods: This research is quantitative research using primary data. The population of this research is MSME taxpayers who are registered at KPP Pratama Manado. Determination of the sample of this study using the slovin formula and obtained a sample of 98 MSME taxpayers with non-probability sampling technique. The data analysis method used in this research is multiple linear regression analysis and moderation test for moderating variables. Data analysis using IBM SPSS 25. Findings: The results of this study indicate that taxation socialization has no effect on MSME taxpayer compliance, tax knowledge does not affect MSME taxpayer compliance, service quality has a positive and significant effect on MSME taxpayer compliance. In the moderating variable, the use of tax incentives is able to moderate the effect of tax socialization, tax knowledge, and service quality on taxpayer compliance. Contribution & Value Added: This study complements the limitations of studies on tax socialization, tax knowledge, service quality and the use of tax incentives in analyzing its relation to MSME taxpayer compliance